INOVASI STRATEGI PEMBELAJARAN AGAMA KRISTEN PADA ANAK USIA DINI BERBASIS PERMAINAN - Grace Lestari Nasution; Natalia Seniatri; Nelsy Kurniawanty; Eli Alka Sattu; Rosaina Mangeja (CV. ADIBA AISHA AMIRA, 2026)
This study aims to examine innovative game-based learning strategies in Christian Religious Education for early childhood through a literature review. Learning at this stage needs to be adjusted to children’s cognitive, socio-emotional, and motor development, making play-based and holistic learning approaches highly essential. The findings indicate that instilling faith values is more effective when delivered through concrete experiences such as Bible stories, prayer, worship songs, and social interaction. Learning innovations through educational games, storytelling, role-play, creative media, and the use of technology can enhance children’s engagement and understanding. These strategies not only support cognitive development but also shape children’s character and spiritual life. Therefore, game-based learning is a relevant and effective approach in Christian Religious Education for early childhood.